Records of the genus Henricia Gray, 1840 (Echinodermata: Asteroidea: Echinasteridae) from Chinese waters - Xiao, Ning; Liao, Yulin; Liu, Ruiyu (Zootaxa, 2011)
Eight species and three subspecies of Henricia Gray, 1840 from Chinese waters are reported: H. arcystata Fisher, H. aspera robusta Djakonov, H. densispina (Sladen), H. exigua Hayashi, H. leviuscula leviuscula (Stimpson), H. leviuscula spiculifera (H.L.Clark), H. ohshimai Hayashi, H. pacifica Hayashi, H. regularis Hayashi, six of which are reported for the first time from Chinese waters. A key to Chinese species of Henricia and photos are provided. Species diversity of echinoderms in China seas is briefly discussed.